Food Enzymes: General Properties and Kinetics - Khade S.M.; Srivastava S.K.; Kamble L.H.; Srivastava J. (My University, 2025)
Enzymes are the biocatalysts having a catalytic power that speeds up a chemical reaction without changing the equilibrium of the reaction. Almost all enzymes are protein in nature and the biocatalytic power lies in the integrity of their structural conformation. The enzymes are highly specific with their substrate molecules that convert into the product by decreasing the activation energy, without getting changed itself. However, the biocatalytic power of the enzymes also depends on several physico-chemical parameters such as temperature, pH, salt concentrations, etc. of the reaction. The enzyme catalysis can be quantitatively revealed by the enzyme kinetics mechanism which measures the reaction rates and the affinity of enzymes towards the substrates and inhibitors. The enzymes can be isolated from the various biological factories such as plant, animal, or microbial cells depending upon the type of enzyme. However, in order to produce at large scale, the microbial sources are the best choice which can effectively reduce the production and purification cost of enzymes. The enzymes are widely used in various sectors such as agriculture, environmental, leather tanning, paper and pulp, chemical and pharmaceutical, detergent, food and beverages, etc. In this chapter, we are mainly focussing on the role of enzymes in the food industry. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2022.